The Breakthrough Listen Search for Intelligent Life: MeerKAT Target Selection. (23rd June 2021) - Czech, Daniel; Isaacson, Howard; Pearce, Logan; Cox, Tyler; Sheikh, Sofia Z.; Brzycki, Bryan; Buchner, Sarah; Croft, Steve; DeBoer, David; DeMarines, Julia; Drew, Jamie; Gajjar, Vishal; et al.
Abstract: New radio telescope arrays offer unique opportunities for large-scale commensal SETI surveys. Ethernet-based architectures are allowing multiple users to access telescope data simultaneously by means of multicast Ethernet subscriptions. Breakthrough Listen will take advantage of this by conducting a commensal SETI survey on the MeerKAT radio telescope in South Africa. By subscribing to raw voltage data streams, Breakthrough Listen will be able to beamform commensally anywhere within the field of view during primary science observations. The survey will be conducted with unprecedented speed by forming and processing 64 coherent beams simultaneously, allowing the observation of several million objects within a few years. Both coherent and incoherent observing modes are planned. We present the list of desired sources for observation and explain how these sources were selected from the Gaia DR2 catalog. Given observations planned by MeerKAT's primary telescope users, we discuss their effects on the commensal survey and propose a commensal observing strategy in response. Finally, we outline our proposed approach toward observing one million nearby stars and analyze expected observing progress in the coming years.